2013
DOI: 10.1186/1471-2156-14-79
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for milk fatty acids in Danish Holstein cattle based on SNP markers using a Bayesian approach

Abstract: BackgroundFor several years, in human nutrition there has been a focus on the proportion of unsaturated fatty acids (UFA) and saturated fatty acids (SFA) found in bovine milk. The positive health-related properties of UFA versus SFA have increased the demand for food products with a higher proportion of UFA. To be able to change the UFA and SFA content of the milk by breeding it is important to know whether there is a genetic component underlying the individual FA in the milk. We have estimated the heritabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 22 publications
(53 reference statements)
7
46
6
Order By: Relevance
“…The milk data are generally in agreement with the values obtained in another study on Danish Holstein (Krag et al 2013b). The average CH 4 production was 395 g per day and the CH 4 production in grams per kilo ECM was 11.04.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The milk data are generally in agreement with the values obtained in another study on Danish Holstein (Krag et al 2013b). The average CH 4 production was 395 g per day and the CH 4 production in grams per kilo ECM was 11.04.…”
Section: Resultssupporting
confidence: 80%
“…This methodology has successfully been applied to fatty acid concentrations in milk fat with moderate estimates of heritability ranging from 0.10 for C18:1 trans-11 to 0.34 for C8:0 and C10:0 (Krag et al 2013b). They showed that the SNP markers capture the population structure well and that SNP markers could be used as an alternative to traditional pedigree-based methods.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Genetic variability has been found to influence the presence of some fatty acids, mainly those originating from de novo mammary fatty acid synthesis (e.g., Stoop et al, 2008;Mele et al, 2009;Krag et al, 2013), and between-breed differences have been observed in milk fatty acid profiles (White et al, 2001;Kelsey et al, 2003;Maurice-Van Eijndhoven et al, 2011). Furthermore, high-level genetic correlations have been observed among fatty acid that share similar metabolic production pathways (Soyeurt et al, 2007;Stoop et al, 2008).…”
Section: Genetic and Environmental Relationships Of Detailed Milk Fatmentioning
confidence: 95%
“…Long-chain fatty acids are derived from blood lipids, which originate principally from the diet and endogenous lipids, and are characterized by low to medium heritability (Soyeurt et al, 2007;Stoop et al, 2008;Mele et al, 2009). Table 1 shows the descriptive statistics and heritability of selected fatty acids according to Krag et al (2013). Each fatty acid is presented by its mean (x ̅ ), standard deviation (s x ) and genomic heritability estimate (h g 2 ), respectively.…”
Section: Introductionmentioning
confidence: 99%